Do friends follow each other? FDI network effects in Central Europe - Gábor Békés; Márta Bisztray (Hungarian Academy of Sciences, Institute of Economics, 2017)
A great deal of multinationals receive a bundle of hidden or cash subsidizes upon investing in a foreign country. Policymakers often argue that a subsidy today will help locate friends of the investor later on. Using extensive data on FDI investments, we analyze such patterns. In particular, we investigate if co-location is more frequent among connected firms such as members of business groups as well as firms sharing similar background. Focusing on investments into Central and Eastern European countries we find evidence of co-location pattern of connected firms.
Keywords: F23; R3; 330; Foreign direct investment; agglomeration; location choice; network effects; business groups